Psychological Interpretation of the Concept of Happiness - Askarova Nargiza Abdivalievna. (Genius Journals, 2023)
At present, the request to study the problem of happiness is associated with an increase in the number of stressful situations, the complexity of designing a person's own life, the choice of life guidelines, the difficulties of socialization, due to radical changes in the structure of social norms and values, one of the reasons for which is intercultural interaction.
Keywords: happiness; socialization; psychological health; emotion